Gregor and the Marks of Secret - Collins Suzanne 1962; Suzanne Collins (London : Suzanne Collins, 2006)
Twelve-year-old Gregor returns to the world beneath New York City, where he joins forces with Princess Lexa and Ripred the rat to defend the Underlanders and the Nibblers from the army led by the adolescent rat king, the Bane.
O
730